Compression of femtosecond ytterbium fibre laser pulses using nonlinear processes in silica fibre. (May 2018) - Didenko, N.V.; Konyashchenko, A.V.; Losev, L.L.; Tausenev, A.V.; Tenyakov, S.Yu.
Abstract: The temporal compression of 100-fs nanojoule laser pulses using nonlinear processes in silica fibre has been studied by numerical simulation and experimentally. The simulation results demonstrate that, in the case of spectral broadening in a normal dispersion fibre, followed by the temporal compression of the pulse in a compressor with a negative second-order dispersion, up to 90 % of the compressed pulse energy can be concentrated in the main peak, whose duration is a factor of 8 shorter than the initial laser pulse duration. In our experiments, 100-fs ytterbium fibre laser pulses have been compressed to pulses with an ∼13-fs main peak accounting for 87 % of the compressed pulse energy. At an average ytterbium laser output power of 4.2 W, the average power at the compressor output has been 3.1 W.